Applied Materials Science : Applications of Engineering Materials in Structural, Electronics, Thermal, and Other Industries - Chung, Deborah, D . L. (Boca Raton, Fla. : CRC Press, c2001., 2017)
238 p. : ill. ; 24 cm.